2022
DOI: 10.1016/j.amjms.2022.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Perception, Prevalence, and Prediction of Severe Infection and Post-acute Sequelae of COVID-19

Abstract: Background : The aim of the study was to assess, characterize, and describe the prevalence and predicting factors of patient-reported severe coronavirus disease 2019 (COVID-19) infection and post-acute sequelae of COVID-19 (PASC). Methods : We prospectively surveyed patients who received care in our outpatient clinic for COVID-19 from March 13, 2020, through August 17, 2020, and then retrospectively reviewed their electronic health records. We collected data for age, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…They found that the acute phase symptom severity and any comorbid disease, including worsened mental health increase the risk of the manifestation of post-COVID symptoms. Another study also confirmed that female sex, depression, and anxiety symptoms increase the risk of the onset of persistent post-COVID symptoms [37]. Our findings partially confirm these results, as in our regression model acute symptomatology and depression might predict the number of long-covid symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…They found that the acute phase symptom severity and any comorbid disease, including worsened mental health increase the risk of the manifestation of post-COVID symptoms. Another study also confirmed that female sex, depression, and anxiety symptoms increase the risk of the onset of persistent post-COVID symptoms [37]. Our findings partially confirm these results, as in our regression model acute symptomatology and depression might predict the number of long-covid symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…We found that COVID-19 severity, even amongst a hospitalized cohort, was an overall predictor of PASC in the group of 242 patients that completed follow-up, as has been described in multiple other cohorts [ 33 35 ]. Although some studies have suggested that PASC may be more common in those with mild disease [ 36 ], we did not have a comparison group of non-hospitalized patients in our cohort to test this hypothesis. Among the subgroup of patients with PASC, the severity of index COVID-19 illness did not appear to predict which patients would have the most symptoms or disability.…”
Section: Discussionmentioning
confidence: 99%
“…While there are several reports of predictors of short term outcomes during hospitalization or within the first months following COVID-19 (e.g. mortality or discharge disposition) [ [24] , [25] , [26] ], as well as reports describing qualitative subjective post-acute COVID symptoms [ 2 , 8 , 9 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ], this study is distinct in that it prospectively explores the impact of life stressors along with demographic, comorbid, and neurological events as predictors of quantitative long-term cognitive, functional, quality of life and post-acute symptoms outcomes in a large population.…”
Section: Discussionmentioning
confidence: 99%
“…We identified female sex as an independent predictor of both anxiety and limitations in activities of daily living. Others have identified that female sex may be a predictor of post-acute COVID-19 symptoms [ 8 , 9 , 27 , 28 , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , 41 ]. In a survey of 999 community dwellers across the U.S, female sex, along with younger age, racial/ethnic minority status, baseline disability, fewer years of formal education, and/or a history of psychiatric disease were significant predictors of post-acute COVID-19 symptoms [ 12 , 32 ].…”
Section: Discussionmentioning
confidence: 99%